Immunological Aspects of Latent Tuberculosis Infection in Diabetes Mellitus - Yunita Arliny (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
AbstractThe interaction of diabetes mellitus (DM) with tuberculosis (TB) is currently a health concern. Diabetes mellitus is one of the main risk factors for TB infection to become latent TB and / or progress to active TB. Immune mechanisms contribute to this increased risk. The disruption of the mycobacteria recognition process, phagocyte activity and cellular activity will affect the disruption of cytokine and chemokine production. Hyperglycemia that occurs will result in delayed adaptive immune response resulting in reduced Th1, Th2, and Th17 cells as well as the cytokines produced by these cells that play a role in macrophage activation and TB inflammatory response. Understanding of the immune mechanisms that underlie the sensitivity of DM to TB infection, especially latent TB, will facilitate the implementation of strategies in screening and therapy to deal with the double burden of both diseases. The purpose of this literature study focuses on the relationship of DM with latent TB infection in terms of immunology.